Myth and Mythography in Contemporary African Drama (2011)
Most previous studies regarded myths as a plethora of concocted stories: they paid little attention to dramatic myth and mythography as productive and effective in African way of life. Modernism, sequestered from the past, created directionless and questioning societies. Solutions, pre-encoded in mythologies and transmitted through generations, were jettisoned. This study, therefore, situates dramatic mythic tendencies, depictions and effects in present African way of lives with a view to highlighting the connectivity of their socioreligious, political, economic and general implications to individual and national lives of the African people. The study employs Carl Jung‟s archetypal model which deals with holistic and universal symbols of human experiences. The collective unconscious is the pooling source of human experiences which manifests different but related forms, while a unit of symbol (the primordial original) is the derivative mold from which others emanate. Nine African dramatic texts, Tewfik al-Hakim‟s Fate of a Cockroach (FOC), Athol Fugard‟s Sizwe Bansi is Dead (SBD), Brett Bradley‟s Ipi Zombi? (IPZ), Ebrahim Hussein‟s Kinjeketile (KIN), Ngugi wa Thiong‟o and Micere Mugo‟s The Trial of Dedan Kimathi (TDK), Femi Osofisan‟s Morountodun (MOR), Efua Sutherland‟s The Marriage of Anansewa (MOA), ‟Zulu Sofola‟s Wedlock of the Gods (WOG) (for feminist related issues) and Wole Soyinka‟s Death and the King‟s Horseman (DKH), were purposively selected because they portray African consciousness in authorship, topicalities and environmental issues. The texts are subjected to content analysis. Mythic encryptions represent, for all levels of life, the people‟s accrued mythic experiences. Myth and mythography become everyday creations that are unlimited to the past as ordinary records and stories. They represent present realities with codifications that impact on life and the future. The texts contain mythic tendencies which reveal mythographic meanings and idiosyncrasies relevant to ongoing national and individual situations. Within the African socio-religious life, rites and rituals, marriages and initiations, births and deaths are models of codification. They are symbolic and mythographic representations to entering next level of physical or spiritual life. This is represented in FOC, KIN and DKH. Adil, Kinjeketile and Olunde respectively become heroes through the death of the self. Human reliance on spiritual forces is curtailed at individual and national stages. The powers and presence of gods in human affairs become demystified: man must fight for political and economic independence as depicted in MOR, MOA and TDK as the characters fight the establishment by creating new mythic stories. Textual mythic findings encourage the discarding of anachronistic socio-religious based mythological ideas: rites, beliefs, patrilineal, racial and ethnic discriminations as portrayed in SBD, WOG and IPZ. Solutions to secular and spiritual developmental problems are pre-embedded in African dramatic textual myths. African life is affected by mythographical codifications that can prevent social eruptions, help maintain social balance and instill peaceful co-existence. Therefore, African myths and mythography should be refined and preserved